The hundred-dollar robber : a mystery with money - Thielbar, Melinda (Thielbar, Melinda. Manga math mysteries., 2010)
Someone has stolen money from the soccer team's car-wash earnings, and the students from Sifu Faiza's Kung Fu School must set aside their feud with the soccer players to figure out how much money was stolen and by whom.